Gammaknife radiosurgery in patients with acromegaly - (:unkn) unknown (ELSEVIER SCI LTD, 2011)
We aimed to evaluate the efficacy and reliability of gamma-knife radiosurgery (GKR) in 22 patients with acromegaly at the Endocrinology-Metabolism Clinic of Cerrahpasa Medical School. We collected data retrospectively from hospital records on disease activity and other pituitary functions, pituitary MRI and visual fields, before GKR and 6, 12, 24, 36,48 and 60 months after GKR. The median follow-up duration after GKR was 60 months (interquartile range [IQR]: 24-60 months). The remission rate was 54.5% after the 60 months of follow-up. The median growth hormone (GH) level at 60 months after GKR (0.99 ng/mL [IQR: 0.36-2.2]) was significantly lower than the median GH level before GKR (5.65 ng/mL [IQR: 3.85-7.2] (p = 0.002). The median insulin-like growth factor-1 (IGF-1) level 60 months after GKR (221.5 ng/mL [IQR: 149-535]) was significantly lower than the median IGF-1 level before GKR (582.5 ng/mL [IQR: 515-655]) (p = 0.008). Tumour growth was well controlled in 20 patients (95.2%). Six patients (28.6%) developed new-onset hypopituitarism. We concluded that GKR is an effective adjuvant treatment to control tumour growth, lower GH and IGF-1 levels, and to increase remission rates in patients with acromegaly who were refractory to surgical and medical treatment. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Acromegaly; Gammaknife radiosurgery; Hypopituitarism; CONVENTIONAL PITUITARY IRRADIATION; GROWTH-FACTOR-I; KNIFE RADIOSURGERY; STEREOTACTIC RADIOSURGERY; TRANSSPHENOIDAL SURGERY; RADIOTHERAPY; HORMONE; MANAGEMENT; OCTREOTIDE; EFFICACY